Legal Protection for Doctors in Health Service Practices - Eriawan Agung Nugroho; Anggraeni Endah Kusumaningrum (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
The advanced developments in technology, information, and knowledge, especially in the fields of health and law, will have a negative impact on the mindset of society, especially in health services. This is proven by the wide variety of demands on medical personnel, the doctors who practice medicine. Cases of suspected malpractice are often over-reported by the mass media and social media. Doctors are seen to have no responsibility or making mistakes in their profession. In fact, all the news that is delivered or written does not necessarily reflect reality. The actions were taken by the doctor corresponds with professional standards and standard for operating procedures. This study aims to explore the analysis of legal protection implementation and its weaknesses in a medical dispute between doctors and patients. This study employed a normative juridical approach by library research. The primary and secondary legal material sources were taken from laws, books, and scientific journals. The findings revealed that in doing medical practice, doctors must fulfill informed consent and medical records. This is to serve as evidence that can exempt the doctors from all lawsuits if malpractice allegations arise. There are many reasons for the repeal of the doctors’ sentences to free them from lawsuits. This includes the risk of medication and medical accidents. In conclusion, a doctor who has carried out his duties based on professional standards, service standards, and standard operating procedures is entitled to proper legal protection based on the value of justice